Sosialisasi Pentingnya Pendidikan pada Siswa-Siswi Kelas 5 dan 6 Sekolah Dasar Negeri 152 Seluma - Bagas Ari Wirakusuma; Fitrian Fitrian; Juliva Erlaili; Dina Az Zahra; Hana Mahdiyahna; Retno Alisya Putri; Ema Yunita Sari; Prisillia Anggraini Putri; Juwita Purnama Sari; Egi Gusta Pratama (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
SDN 152 Seluma, Tawang Rejo Village, wanted to increase students' awareness and desire to learn, especially for students in grades 5 and 6, who will continue to junior high school. As part of the Community Service Program (KKN) group 135, this activity was held on July 31, 2024. Field survey, preparation, and socialization activities were conducted. The activity was presented interactively through educational games, discussions, and lectures. The survey results showed that most students do not have enough motivation to study and do not understand the importance of studying seriously. Through interesting and engaging methods, this community successfully raises students' awareness about the importance of education. The success of this activity depends on the active participation of students and support from teachers and parents. It is hoped that this activity will encourage students to study harder and continue their education to a higher level.